Nursing Leadership and Its Impact on Healthcare Quality: A Systematic Review - Hashlan, Mohammed AbdulAlrahman; Alqhtani, Naseer Ali; Alshaiban, Ameen Mohammed; Alqahtani, Mohammed Murayyi Saeed; Alqahtani, Mohammed saad Mohammed; Alward, Hussein Nasser Mohammed; Al Qahtani, Majed Mushabbab Ali; Alqahtani, Mohammed Saeed Mohammed; Hadi, Rakan Lahiq bin Lahiq; Assiri, Adel Hadi Mohammed; Alrashidi, Sultan Ibrahim; Altamimi, Bassam Bader; et al. (Journal of Ecohumanism, 2024)
Nursing leadership plays a crucial role in shaping healthcare quality, directly impacting patient outcomes, staff satisfaction, and organizational performance. This systematic review explores the relationship between various nursing leadership styles and healthcare quality metrics, including patient safety, clinical outcomes, and team dynamics. By synthesizing findings from recent studies, the review identifies transformational and servant leadership as the most effective styles for fostering positive healthcare outcomes. It also highlights challenges, such as limited leadership training and organizational barriers, and offers actionable recommendations for integrating leadership development into nursing education and practice. These insights aim to guide healthcare organizations in adopting evidence-based leadership models to enhance overall care quality.